Aplicação de nitrogênio em forrageiras e produção da cultura da soja em sucessão no sistema plantio direto - Tanaka, Katiuça Sueko [UNESP] (2015)
The palissade grass have good performance to compose production systems such as no-tillage and crop-livestock integration, due to the high dry matter production, providing good coverage to the ground. Since nitrogen is responsible for the growth of plants, fertilization with this nutrient may favor larger mass of dry matter production of palisade grass and consequently provide high amounts of plant residue to the soil cover. The aim of this work was to evaluate the viaibility of early application of nitrogen in the production of straw plant, in order to introduce nitrogen into the system and assess the soybean yield in response to the management of nitrogen. This study was conducted in the agricultural years 2013/2014 and 2014/2015, the Lageado Experimental Farm, belonging to the College of Agricultural Sciences - UNESP, located in Botucatu - SP. The experimental design was a randomized block in a factorial 2x6 with four replications. The treatments consisted of ammonium nitrate application times (control, fertilization at sowing and coverage, 20 days before the desiccation, 10 days before the desiccation, five days before the drying and one day before sowing) in two palisade grasses (U. brizantha cv. Marandu and U. ruziziensis). The following evaluations were performed on forage plants: dry matter production and macronutrients levels; and soybean was determined dry matter, macro and micronutrients levels, plant height and yield components (final plants population, number of pods per plant, number of seeds per pod, weight of 100 grains and productivity) . With this study concludes: U. brizantha produced higher amounts of dry matter and greater accumulation of nutrients in straw; soybeans performed better when sown on the U. brizantha and applying nitrogen fertilizer at different times ...